1992
DOI: 10.1007/bf02190252
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in patients with schizophrenia

Abstract: Regional cerebral blood flow was evaluated using Tc99m-HMPAO SPECT in 10 medicated patients with schizophrenia and 9 healthy volunteers. There were no prefrontal regions in the patient group with lower regional indices than in the control group. However, in the left hippocampal region, relative blood flow was significantly increased in the patient group compared with the control group. Furthermore, there was a relative increase in blood flow in the left basal ganglia of the patient group. A negative correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 19 publications
2
36
1
1
Order By: Relevance
“…We found that GAD 67 mRNA levels were sig nificantly reduced in the DG in the schizophrenia group and in CA4 in the schizophrenia and major depression groups. These reductions in GAD 67 expression may have implications for neuroimaging studies that show an increase in hippocampal activity during the retrieval of words, 10,51 auditory hallucinations 13 and rest [52][53][54][55] in individuals with schizophrenia. Together these results indicate that the abnormal activity seen in individuals with schizophrenia may be due to a decrease in the inhibitory tone mandatory for normal hippocampal function.…”
Section: Discussionmentioning
confidence: 93%
“…We found that GAD 67 mRNA levels were sig nificantly reduced in the DG in the schizophrenia group and in CA4 in the schizophrenia and major depression groups. These reductions in GAD 67 expression may have implications for neuroimaging studies that show an increase in hippocampal activity during the retrieval of words, 10,51 auditory hallucinations 13 and rest [52][53][54][55] in individuals with schizophrenia. Together these results indicate that the abnormal activity seen in individuals with schizophrenia may be due to a decrease in the inhibitory tone mandatory for normal hippocampal function.…”
Section: Discussionmentioning
confidence: 93%
“…A number of investigators who have used functional neuroimaging with schizophrenia patients have reported abnormalities in metabolic rates or blood flow in the striatum (42)(43)(44)(45). Some investigators have noted reduced blood flow or metabolism in the caudate (44,46), although others have reported increased striatal blood flow or metabolism among schizophrenia patients (45,47).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have noted reduced blood flow or metabolism in the caudate (44,46), although others have reported increased striatal blood flow or metabolism among schizophrenia patients (45,47). The reasons for the discrepant findings with regard to the direction of metabolic and blood flow abnormalities across studies are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The positive syndrome has been correlated with increased rCBF in the medial temporal lobe (Kawasaki et al 1992;Liddle et al 1992a and ventral striatum (Liddle et al 1992b;Busatto et al 1995) of patients with schizophrenia, and patients with prominent positive symptoms exhibit abnormal temporal lobes in MRI scans (Wible et al 1995). Recent studies using PET scans during hallucinations revealed activation of the thalamus, putamen, accumbens, and hippocampus (Silbersweig et al 1995), in addition to auditory cortical regions (Suzuki et al 1993).…”
Section: Model Of the Neurobiological Systems Proposed To Underlie Thmentioning
confidence: 99%
“…Although some studies using positron emission tomography (PET) showed no alteration in basal regional cerebral blood flow (rCBF) in the PFC (Kawasaki et al 1992), hypofrontality in schizophrenia can be observed as an absence of increase in rCBF during the WCST (Berman et al 1986) and as an impaired functional MRI activation in verbal fluency tasks (Yurgelun-Todd et al 19966). Alterations in phosphomonoesters (Pettegrew et al 1991) and N-acetyl aspartate (Buckley et al 1994) in magnetic resonance spectroscopy (MRS) studies provide further evidence for prefrontal cortical dysfunction.…”
Section: Cortical Disturbances In Schizophreniamentioning
confidence: 99%